Personality traits and resilience mediated by depressive symptoms in a sample of psychotherapy patients: A cross-sectional study. - Leonardo Gonçalves; Vitória Maria Tabosa Evaldt; Neusa Sica da Rocha (PLoS ONE)
Introduction Resilience is a concept that has been widely studied in different contexts and is related to adaptation to different stress levels. Although research in psychotherapy has produced vast knowledge about the effectiveness and mechanisms that mediate response, there is still no clarity about the role of resilience in this process, especially research in psychotherapy with patients with severe mental illness. Due to the implications of severe mental illness in different areas of life, in these patients, the capacity for resilience may be impaired, and the mechanisms involved in mediating this process are still not well explained. Objective Verify the associations between personality traits and resilience and their potential confounders (sociodemographic factors, pharmacological treatment, type of psychotherapy, social support, depressive and anxiety symptoms). Assess depressive symptoms as a possible mediator of the relationship between personality traits and resilience. Methods This is a naturalistic cross-sectional study, with 83 participants undergoing psychotherapy from different theoretical lines (psychodynamic, cognitive-behavioural, and interpersonal). Sociodemographic characteristics were evaluated, as well as resilience (25-item Connor Davidson Resilience Scale), depressive symptoms (Beck Depression Inventory), anxious symptoms (Beck Anxiety Inventory), and Personality traits (Personality Inventory for DSM-5). Results Resilience was negatively associated with depressive symptoms (B = -12.1, p < 0.001). The mediation effect was significant for depressive symptoms (b = -7.21, BCa 95% CI [-12.6, -3.07]). This variable mediated approximately 46% of the relationship between negative affectivity and resilience. Conclusion Resilience was positively associated with antagonism traits and negatively with negative affectivity and depressive symptoms. Depressive symptoms mediated 46% of the relationship between negative affectivity and resilience. The main findings of this study contribute to a greater understanding of the mechanisms involved in resilience, thus influencing the mental health outcomes of patients with severe mental illness.